Leveraging oyster shell and zero-valent iron to eliminate excessive acidification and enhance methane production from readily acidified substrates - Ding, Xiaofan (Environmental technology, 2024)
Anaerobic digestion is a sustainable technology for methane (CH4) production from organic waste and wastewater. However, its performance is frequently hindered by excessive acidification in readily acidified substrates, such as starch wastewater. Oyster shell (OS), a natural alkaline material, effectively regulates pH and enhances CH4 production. Nevertheless, its use increases CO2 levels in biogas, highlighting the need for in-situ conversion of CO2 into CH4. This study presents a novel approach by combining OS with zero-valent iron (ZVI), which acts as an indirect hydrogen (H2) source, to facilitate this conversion and boost methanogenesis from readily acidified substrates. Results demonstrated a 22.8% reduction in CO2 levels and a significant increase in CH4 yield to 364 mL/g-COD, surpassing both previously reported values and the theoretical maximum of 350 mL/g-COD. Additionally, the daily CH4 production rate was increased by 60.3%, with a shorter lag phase and overall duration. This improvement was driven by the synergy between OS and ZVI, which enhanced hydrogen ion consumption, releasing additional CO2 and H2 for methanogenesis. The synergistic interaction also promoted extracellular polymeric substances levels, acidogenic and methanogenic steps, key enzyme activities, and enrichments of Methanothrix, hydrogenotrophic methanogens, and Longilinea. Furthermore, an economic assessment revealed significant cost benefits of this approach, offering promising potential for industrial applications. This study provides new insights into leveraging OS and ZVI to eliminate excessive acidification and improve CH4 production from readily acidified substrates